PENERAPAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KREATIVITAS DAN KOLABORASI SISWA PADA MATERI ZAKAT FITRAH DI SMKN PP CIANJUR - Aryani, Wiwik Dyah; Sahdan, Sahdan; Susanti, Susanti; Gunawan, Apip (Penerbit Widina, Widina Media Utama, 2025)
This study aims to describe the implementation of the Project Based Learning (PjBL) model in improving students’ creativity and collaboration in the topic of zakat fitrah within Islamic Religious Education learning at SMKN PP Cianjur. This research uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation.The results showed that the PjBL model is effective in fostering students’ creativity through various project activities such as creating zakat educational media, simulating zakat distribution, and presenting zakat fitrah campaigns. Moreover, PjBL encourages active and productive student collaboration through group work, deliberation, and fair division of roles within teams. Islamic religious values such as responsibility, empathy, and cooperation are also internalized during the learning process.In conclusion, the implementation of PjBL in zakat fitrah learning creates a contextual, participatory, and meaningful learning process. This model can be an innovative alternative in developing Islamic Religious Education strategies oriented towards 21st-century skill enhancement.ABSTRAKPenelitian ini bertujuan untuk menganalisis penerapan Project Based Learning (PjBL) dalam meningkatkan kreativitas dan kolaborasi siswa pada materi zakat fitrah dalam pembelajaran Pendidikan Agama Islam. Metode yang digunakan adalah studi kasus dengan pendekatan kualitatif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan PjBL efektif meningkatkan kreativitas siswa melalui kegiatan proyek seperti pembuatan media edukasi zakat, simulasi distribusi zakat, dan kampanye zakat fitrah. Selain itu, model ini mendorong kolaborasi aktif antar siswa melalui kerja kelompok, musyawarah, dan pembagian peran yang adil. Nilai-nilai religius seperti tanggung jawab dan empati turut terinternalisasi selama pembelajaran. Model PjBL terbukti menciptakan pembelajaran yang kontekstual, partisipatif, dan bermakna, serta relevan untuk penguatan keterampilan abad ke-21 dalam pembelajaran Pendidikan Agama Islam.